AIR SUMBER KEHIDUPAN (Tinjauan Kimia Air dalam Al-Qurâ€™an) - Astuti, Rini Nafsiati (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2008)
The living process is mediated by water to start a long evolutionary line that connected animal, plant, as well the human being. The beginning of life that involved water reflected in all of the life process, such as animal, plant, and human being as well. Single-cell organism is the simplest living thing is surrounded and filled with water. In order to survive, plant has to take water from the ground. While human being's body contains water about 54 % of weight contains liquid. Without water, living thing will not survive. The molecule of water bonds together in a special way that is known as hydrogen bonding. If there is no hydrogen bonding between water molecules so at 1 atm pressure water will be boiling at 100Â° C. This condition can cause disaster to the life on earth, such as blood will be boiling in the body, plants will be wilted and died, and the world will be turn to dry desert. Human no longer can't make their drinks. Water is very important for human life as it reflected in the verse that suggest human being to note the water they drink stated in Qur' an.